World Economy Spring 2023: Stubborn inflation, moderate growth - Klaus-Jürgen Gern; Stefan Kooths; Jan Reents; Nils Sonnenberg; Ulrich Stolzenburg (Kiel Institute for the World Economy (IfW Kiel), 2023)
The recovery of the global economy from the Covid crisis came to an end in 2022 amid high energy prices and great uncertainty. While the energy crisis is easing, the effects of monetary policy, which was tightened rather late but then very quickly, are now increasingly weighing on growth. World output slowed to a crawl toward the end of the year and is expected to expand only moderately in the current year despite a post-Covid revival in China. Measured on a purchasing power parity basis, we anticipate global growth of 2.5 percent in 2023, following 3.2 percent last year. We have raised our forecast for 2023 by 0.4 percentage points from December, partly because of the improved situation on energy markets and partly because the economy in the United States has proved more robust than expected. Our forecast for 2024 remains unchanged at 3.2 percent. Although inflation is likely to fall significantly in the coming months thanks to lower commodity prices, underlying inflation is likely to remain high for the time being and will not return to near the target levels before the end of the forecast horizon.
Keywords: 330; advanced economies; emerging economies; monetary policy